Infant observation through a screen; an online response to the impossibility of in-person observation during the Covid 19 pandemic of 2020–2021 in northern Italy. Issue 1 (2nd January 2021) - Gatti, Patrizia
ABSTRACT : This article is based on observational accounts written after video-observations during the Covid-19 pandemic emergency in northern Italy in 2020–2021. The author tries to show what happened at both sensory and relational levels between observers and infants and between observers and families. Her reflections also consider the observation students' training experience and a creative response to ensuring attainment of the educational goals of their linked university-validated course. The Covid pandemic forced everyone to readjust and renegotiate some of the basic tenets of infant observation. Physical distance and the lack of in-person contact inevitably changed the 'proper' emotional distance as well as the management of silence and abstention (from initiating action or conversation). The article's intention is to focus on some critical aspects of observing through a screen, which was never Esther Bick's intention at its introduction. The use of online observation through a screen clearly requires further examination to better understand the novel experience forced on observers as a means of trying to continue baby observation during the pandemic.